Studi Deskriptif Kreativitas Peserta Didik Pada Batik Dedaunan Menggunakan Teknik Ecoprint Kelas V SDN 25 Kota Bengkulu - Sabila, Neta; Tarmizi, Pebrian; Kurniawati, Ike (Universitas Bengkulu, 2025)
This study aims to describe the creativity involved in the process of making leaf-patterned batik using the ecoprint technique among fifth-grade students at SDN 25 Kota Bengkulu. The research employs a descriptive qualitative approach, with the participants being fifth-grade students. Data collection instruments include observation, interviews, and documentation. Data analysis was conducted through data collection, reduction, presentation, and verification, with data validity ensured through triangulation and member checking. Creativity was analyzed based on four indicators: fluency, flexibility, originality, and elaboration. In terms of fluency, Group 1 quickly agreed on a main idea, while Groups 2 and 3 showed more dynamic discussions. Flexibility was observed in all groups' ability to adapt to various challenges throughout the process. Originality was evident in the design ideas, choice of leaves, and motif arrangements, all of which were developed independently without interference from teachers or other groups. Elaboration was shown through the addition of various types of leaves to enrich the details and meaning of the design, as well as strategic adjustments during the drying process to ensure clean and optimal results. In conclusion, each group demonstrated different combinations of creativity indicators during the batik-making process. More than one indicator of creativity could emerge within a single process for each group.